1983
DOI: 10.1146/annurev.iy.01.040183.002341
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Structures Involved in T-Cell Activation

Abstract: FOREWORDWhereas the discussion of epitope-antigen structure relating to B cells would not be very different from a similar consideration a decade ago, the nature of T-cell recognition and activation by "antigen" encompasses a completely altered area of concern. Within the past 10 years, concepts of restriction to major histocompatibility-complex MHC molecules and in volvement of T cells in idiotypic interactions have revolutionized the view of the "antigen" that activates the T cells.In this article we use a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 79 publications
(98 reference statements)
1
20
0
Order By: Relevance
“…However, whereas the 185-kDa SA elicits both helper and suppressor activities, the 4-kDa SA peptide elicits only helper activity [8]. These results were comparable with those reported for P-galactosidase, in that a large 90 amino acid (AA) peptide induces both helper and suppressor T cell activities, whereas a 9 AA peptide (44-52) activates only helper activity [9]. An 11 AA peptide (27-37) which induces suppressor function was also identified.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, whereas the 185-kDa SA elicits both helper and suppressor activities, the 4-kDa SA peptide elicits only helper activity [8]. These results were comparable with those reported for P-galactosidase, in that a large 90 amino acid (AA) peptide induces both helper and suppressor T cell activities, whereas a 9 AA peptide (44-52) activates only helper activity [9]. An 11 AA peptide (27-37) which induces suppressor function was also identified.…”
Section: Introductionsupporting
confidence: 57%
“…Distinct peptide determinants have been identified in generating T cell helper and suppressor functions with P-galactosidase [9], lysozyme [16] and hepatitis B surface antigen [17]. First we identified the 185-kDa SA determinants responsible for T cell helper and suppressor activities [5, 181. This was followed by separation of the small molecular mass (3.8 kDa) SA which elicited only T cell helper and no suppressor activity, both in natural immunity of human subjects and in active immunization of rhesus monkeys [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the recognition ofpeptide antigens is controlled by immune response genes and is often restricted to a given major histocompatibility complex haplotype (20), it is unclear whether a single peptide fragment can be applied as a vaccine in an outbred population. We have previously shown that mice immunized with liposomes containing herpes simplex virus I (HSV-1) or HSV-2 peptides are protected against a lethal HSV-2 challenge and that Lyt-2' cells, and not antibody, are responsible for this protection (21).…”
Section: Discussionmentioning
confidence: 99%
“…the differenc� in regulatory T-cell responses of responder versus nonresponder mice and the opportunity to study nearly pure suppressor T-cell responses in nonrespondel mice-have proven most useful for t h e study of immune regulation. Other well-characterized suppressor T-cell systems also utilized antigens the response to which is under H-2-linked Ir gene control (23,89). Splenic cell extracts from GAT nonresponder mice yield suppressor T-cell factors that fu nction in vivo and in vitro (90).…”
Section: Suppressor T-cell Subsetsmentioning
confidence: 99%